PENGARUH OPTIMISME DAN EMPATI TERHADAP EFIKASI DIRI SISWA SEKOLAH SEPAK BOLA (SSB) BATURETNO BANGUNTAPAN YOGYAKARTA - I Wayan Putra Agustika; TA. Prapancha Hary A (JURNAL SPIRITS, 2012)
ABSTRACTThe purpose of this study was funding the effect of optimism and empathy for students' self-efficacy School Football (SSB) Baturetno Banguntapan Yogyakarta. The samples used in this study is 113 students Football School Baturetno Banguntapan Yogyakarta. The sampling technique used in this study was purposive sampling. The analysis of the data used in this study is the multiple linear regression.The results showed that empathy and optimism had a significant influence on students ' self-efficacy football school. It can be seen from the coefficient R2 = 0.583 and p = 0.001, which means that given the effective contribution of 58.3%. With these results we can conclude that optimism and empathy have an influence on students' self-efficacy football school (SSB) Baturetno Banguntapan Yogyakarta.Â Keywords: empathy, optimism, self-efficacy